Building capacity for clinical research in developing countries: the INDOX cancer research network experience - Raghib Ali; Alexander Finlayson; on behalf of the INDOX Cancer Research Network (Taylor & Francis Group, 2012)
Transnational Organisations increasingly prioritise the need to support local research capacity in low and middle income countries in order that local priorities are addressed with due consideration of contextual issues. There remains limited evidence on the best way in which this should be done or the ways in which external agencies can support this process.We present an analysis of the learning from the INDOX Research Network, established in 2005 as a partnership between the Institute of Cancer Medicine at the University of Oxford and India's top nine comprehensive cancer centres. INDOX aims to enable Indian centres to conduct clinical research to the highest international standards; to ensure that trials are developed to address the specific needs of Indian patients by involving Indian investigators from the outset; and to provide the training to enable them to design and conduct their own studies. We report on the implementation, outputs and challenges of simultaneously trying to build capacity and deliver meaningful research output.